Surge Protection for Low Voltage Systems - Rousseau, Alain (IET energy engineering series, 2021)
Protection of low-voltage electrical and electronic equipment and systems from lightning strikes and other power surges is vital for computing, telecommunications, transportation, power grids, distributed energy and charging installations. This systematic treatise covers surge causes, risk assessment, and protective measures